2021
DOI: 10.1111/cbdd.13923
|View full text |Cite
|
Sign up to set email alerts
|

99mTc‐labeled antibiotics for infection diagnosis: Mechanism, action, and progress

Abstract: Discovery of penicillin marked a turning point in the history of infection therapy which also led to the emergence of bacterial resistance. It is now 100 years to fight with ever‐muted variants of pathogens by developing more and more antibiotics. Since 1987 to todate, no successful class of antibiotic was introduced; this three decade period is known as “the discovery void” period. While, the clinically approved antibiotics are gradually dying in front of bacterial resistance due to which bacterial infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 159 publications
0
12
0
Order By: Relevance
“…These compounds were prepared by reacting norfloxacin with HYNIC active esters (compound 1) under alkaline conditions. The final product was identified by 1 H NMR, 13 C NMR, and ESI-HRMS (related spectra for structural characterization are presented in Supporting Information, Figures S1−S3, respectively), and the results showed that the target ligand was successfully synthesized.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were prepared by reacting norfloxacin with HYNIC active esters (compound 1) under alkaline conditions. The final product was identified by 1 H NMR, 13 C NMR, and ESI-HRMS (related spectra for structural characterization are presented in Supporting Information, Figures S1−S3, respectively), and the results showed that the target ligand was successfully synthesized.…”
Section: ■ Resultsmentioning
confidence: 99%
“…NMR spectrum of compound 2 HYNICNF,13 C NMR spectrum of compound 2 HYNICNF, ESI-HRMS spectrum of compound 2 HYNICNF, in vitro stability in saline 6 h HPLC patterns of three complexes, in vitro stability in the mouse serum 6 h HPLC patterns of three complexes, biodistribution results of [ 99m Tc]Tc-tricine-TPPTS-HYNICNF, biodistribution results of [ 99m Tc]Tctricine-TPPMS-HYNICNF, biodistribution results of [ 99m Tc]Tc-EDDA-HYNICNF, and biodistribution results of [ 99m Tc]Tc-ciprofloxacin, [ 99m Tc]Tc-norfloxacin, and [ 99m Tc]Tc-citrate (PDF)■ AUTHORINFORMATION …”
mentioning
confidence: 99%
“…An antimicrobial drug, that is, methamphetamine (MET) normally applied in the medication of periodontal treatment (Bottino et al, 2012;Freeman et al, 1997). Metronidazole benzoate performs upon anaerobic Grampositive and anaerobic Gram-negative bacteria (P. gingivalis) (Bottino et al, 2012;El-Kamel et al, 2007;Naqvi, 2021). Certainly, the incidence of periodontal pathogens, for example, P. intermedia and P. gingivalis may adversely affect the accomplishment of tissue regeneration (Bottino et al, 2012;Haffajee & Socransky, 1994;Pihlstrom et al, 2005;Slots et al, 1999).…”
Section: Addition Of Antimicrobial Drugsmentioning
confidence: 99%
“…In addition to these clinically available radiopharmaceuticals there has been a decadeslong effort to develop more specific imaging agents with some examples being radiolabeled antibiotics and antimicrobial peptides for bacterial imaging, radiolabeled anti-fungals for fungal infections imaging, radiolabeled pathogen-specific antibodies and molecular engineered constructs. Several excellent reviews on these agents which are primarily still in the preclinical stage have appeared in the last decade (4)(5)(6). In this opinion piece, we would like to discuss some examples of the work published in the last decade on developing nuclear imaging agents for bacterial, fungal and viral infections in order to generate more interest among nuclear medicine community toward conducting clinical trials of these novel probes, as well as toward developing novel radiotracers for imaging infections.…”
Section: Introductionmentioning
confidence: 99%